External assessment form for hospital-based industrial training assessment, Bachelor Optometry (Honours), International Islamic University Malaysia - Md Mustafa, Md Muziman Syah; Yusof, Firdaus (2020)
External assessment form for hospital-based industrial training assessment is developed as a tool to evaluate the clinical performance of optometry students during industrial training at the Ministry of Health facilities, private hospital, private eye clinic and also LASIK centre. This assessment form will be provided to the respective external assessor or local preceptor.